The corporate image of UiTM Kuala Terengganu; a study of the students' satisfaction and loyalty / Siti Rapidah Omar Ali, Wan Zuhaila Wan Abd Rahman and Zulhamri Abdullah - Omar Ali, Siti Rapidah; Wan Abd Rahman, Wan Zuhaila; Abdullah, Zulhamri (2012)
Over the last few years, institutional image has become an important element to the competitiveness of higher education institutions. The situation needs for the universities to focus on establishing a strong corporate image by highlighting students' satisfaction and loyalty. This study examined the relationship between the students' satisfaction and loyalty towards the corporate image of UiTM Kuala Terengganu (UiTMKT). A sample of 306 students was selected among undergraduate students of UiTMKT. The findings showed that students' satisfaction and loyalty were found to be significant drivers of the corporate image of UiTMKT in which students' loyalty emerged as the main predictor. The findings also confirmed the positive relationship between students' satisfaction and loyalty towards corporate image of UiTMKT. As such, the university has to focus on stakeholder imperative because students' satisfaction and loyalty can give a considerable impact to corporate image of the university.